Efficacy of Trichoderma spp. consortium as potential biocontrol agents of Ganoderma disease of oil palm, and involvement of antioxidant enzymes and total phenolic content - Musa, Habu (2017)
Oil palm (Elaeis guineensis) is an economically important cash crop, grown primarily for its oil and has become one of the main oil crop in the world. Unfortunately, a major constrain faced by oil palm industry particularly in Malaysia and Indonesia is the devastating disease known as Ganoderma disease caused by Ganoderma spp. To date, this disease has been causing considerable oil palm yield losses and collapse of oil palm trees, consequently affecting its contribution to the producer’s economy. Thus, research on sustainable and eco-friendly remedy to counter Ganoderma disease is on the upsurge to avoid the current control measures via synthetic fungicides. Trichoderma spp. have been the most studied and valued microbes as biological control agents in an effort to combat a wide range of plant diseases sustainably. In addition, knowledge on Trichoderma’s mechanism employed to act as biological control agent, could be useful in improving on their ability as potent biological control agents against Ganoderma spp. Therefore, in this current study, the potential of Trichoderma spp.(Trichoderma asperellum, Trichoderma harzianum, and Trichoderma virens) as a consortium approach was evaluated as biological control agents against Ganoderma disease on oil palm with these objectives: i) To characterize and identify the selected Trichoderma spp. via morphological and molecular characterization, ii) To evaluate their bio-inoculant potential as oil palm seedling treatment for the control of Ganoderma disease and iii) To study the effects on vegetative growth and suppression of Ganoderma boninense infection in oil palm seedlings treated with Trichoderma spp. as single or consortium application.